1968
DOI: 10.1139/f68-145
|View full text |Cite
|
Sign up to set email alerts
|

Marine Phytoplankter Fatty Acids

Abstract: Twelve species of marine unicellular algae have been cultured under comparable conditions and the total fatty acids determined b1' gas liquid chromatography. Some specific fatty acid relationships paralleling taxonornic groupings were detected but generally individual fatty acids within various algal classes shorved large relative variations. The four Bacillariophyceae examined were notable for fatty acid cornpositions giving iodine values (150, rvhereas in eight other classes the iodine values were all approx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
145
2

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 430 publications
(163 citation statements)
references
References 0 publications
13
145
2
Order By: Relevance
“…In order to get information on the proportion of marine organic carbon we use the diatom-specific fatty acids cis-9-hexadecenoic acid (C 16:1(nÀ7) ), cis-11-hexadecenoic acid (C 16:1(nÀ5) ), and all-cis-5, 8,11,14,17-eicosapentaenoic acid (C 20:5(nÀ3) ) for interpretation (Kates and Volcani, 1966;Ackman et al, 1968;Kattner et al, 1983;Fahl and Kattner, 1993;Graeve et al, 1994). All fatty acid components up to carbon chain length of 22 were determined in this study, however, and the data are available on doi:10.1594/PANGAEA.602289.…”
Section: Methodsmentioning
confidence: 99%
“…In order to get information on the proportion of marine organic carbon we use the diatom-specific fatty acids cis-9-hexadecenoic acid (C 16:1(nÀ7) ), cis-11-hexadecenoic acid (C 16:1(nÀ5) ), and all-cis-5, 8,11,14,17-eicosapentaenoic acid (C 20:5(nÀ3) ) for interpretation (Kates and Volcani, 1966;Ackman et al, 1968;Kattner et al, 1983;Fahl and Kattner, 1993;Graeve et al, 1994). All fatty acid components up to carbon chain length of 22 were determined in this study, however, and the data are available on doi:10.1594/PANGAEA.602289.…”
Section: Methodsmentioning
confidence: 99%
“…Coombs et al (1967) reported that the lipid content of the diatom Navicula pelliculosa increased by about 60% during a 14 h siliconstarvation period. In addition to nutrition, fatty acid and lipid composition and content were also found to be influenced by a number of other factors such as light (Constantopolous and Bloch, 1967;Nichols, 1965;Pohl and Wagner, 1972;Rosenberg and Gouaux, 1967) and low temperatures (Ackman et al, 1968). With the advent of the oil embargo in the early 1970s, a search for alternative energy sources set the stage for an almost twenty-year research effort devoted to biofuel production from algal lipids.…”
Section: Historical Perspective and Recent Advancesmentioning
confidence: 99%
“…Ž 1995 , the short-chain saturated and monorpoly-. unsaturated compounds are commonly related to a Ž marine source e.g., Kates and Volcani, 1966;Ackman et al, 1968;Harrington et al, 1970;Pohl and Zurheide, 1979;Falk-Petersen et al, 1987;Fraser et . al., 1989;Volkman, 1989;Fahl and Kattner, 1993 .…”
Section: Biomarkers As Organic-carbon Source and Environmental Indicamentioning
confidence: 99%